Evolution and Development of Dual Ingestion Systems in Mammals: Notes on a New Thesis and Its Clinical Implications - Jeffrey R. Alberts; Rita H. Pickler (International Journal of Pediatrics)
Traditionally, the development of oral feeding is viewed as a continuous, unitary process in which reflex-dominated sucking behavior gives rise to a more varied and volitional feeding behavior. In contrast, we consider the thesis that the infant develops two separable ingestive systems, one for suckling and one for feeding. First, we apply an evolutionary perspective, recognizing that suckling-feeding is a universal, mammalian developmental sequence. We find that in mammalian evolution, feeding systems in offspring were established prior to the evolution of lactation, and therefore suckling is a separable feature that was added to feeding. We next review an experimental literature that characterizes suckling and feeding as separable in terms of their topography, sensory controls, physiological controls, neural substrates, and experience-based development. Together, these considerations constitute a view of “dual ingestive systems.” The thesis, then, is that suckling is not a simple precursor of feeding but is a complete behavior that emerges, forms, and then undergoes a dissolution that overlaps with the emergence of independent feeding. This thesis guides us to focus differently on the challenges of properly managing and facilitating oral ingestion in infants, especially those born preterm, prior to the developmental onset of suckling.